COMFORT ZONE DAN MENTAL BLOCK YANG TERCERMIN DALAM NOVEL THE CAVE KARYA JOSE SARAMAGO (Sebuah Studi Semiotik Sastra) - Sarif Syamsu Rizal (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2015)
This paper entitled â€œKeterperjaraan Pikiran sebagai Comfort Zone dan Ketakutan Perubahan sebagai Mental Block yang Tercermin dalam Novel â€˜The Caveâ€™ Karya Jose Saramagoâ€ emerges primary signifier representing other signs, and dimension relationship of syntagm and paradigm realized in the novel â€œThe Caveâ€. Theapproaches used to solve the problem are intrinsic and semiotic approaches. The methods of data collecting are library research and documentation. The presentation of data processing result is descriptive research report. The result this paper is solution from signification analysis consisting of the significance of the sign â€œGoaâ€as icon, index, and symbol and the scheme of syntagm and paradigm dimension relationship and their significance. Seen from the relationship, writer finds the message in story that is two matters which sometime cannot go together; those are tradition and modernization, because during civilized historical journey of human being, the modernization often breaks the tradition. The challenge is how to make them coexisting and accepting each other. Modernization or become modern will be able to be accepted and can become the change for the world if sustained by tradition, moreover, if the tradition has been owned and has grown on its nation.Keywords: primary signifier, icon, index, symbol, paradigm, syntagm.